Perancangan Antarmuka Web Visualisasi Grafik Susut Listrik PT PLN UP3 Lubuk Pakam dengan Design Thinking - Daffa Anugraha; Heri Santoso (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
The development of information technology encourages PT PLN (Persero) UP3 Lubuk Pakam to improve efficiency in monitoring electricity loss and cumulative energy data. Currently, data presentation is still manual and less interactive, making the analysis and decision-making process more difficult. This study aims to design a web interface that presents loss data visualization dynamically and comprehensibly. The method used is Design Thinking, which consists of five stages: Empathize, Define, Ideate, Prototype, and Test. These stages are carried out iteratively and focus on user needs. The final result is a web interface prototype featuring interactive charts, simple navigation, and a login system to restrict data input access. The trial results show that the design is simple, responsive, and helps users quickly understand the data. This design is expected to support work efficiency and improve the quality of decision-making within PLN UP3 Lubuk Pakam.